2023
DOI: 10.32604/cmc.2023.032822
|View full text |Cite
|
Sign up to set email alerts
|

Shared Cache Based on Content Addressable Memory in a Multi-Core Architecture

Abstract: Modern shared-memory multi-core processors typically have shared Level 2 (L2) or Level 3 (L3) caches. Cache bottlenecks and replacement strategies are the main problems of such architectures, where multiple cores try to access the shared cache simultaneously. The main problem in improving memory performance is the shared cache architecture and cache replacement. This paper documents the implementation of a Dual-Port Content Addressable Memory (DPCAM) and a modified Near-Far Access Replacement Algorithm (NFRA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The cache coherence protocols cause a larger delay because each core must notify other cores of any changes it makes to a shared variable. The authors in [3] suggested a new coherency approach in the MPCAM that guarantees the cache coherence for all shared variables over multi-core. With this method, there is no longer a need for cache coherence operations, and the delay of accessing the shared cache becomes the same as accessing the core's private memory.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The cache coherence protocols cause a larger delay because each core must notify other cores of any changes it makes to a shared variable. The authors in [3] suggested a new coherency approach in the MPCAM that guarantees the cache coherence for all shared variables over multi-core. With this method, there is no longer a need for cache coherence operations, and the delay of accessing the shared cache becomes the same as accessing the core's private memory.…”
Section: Related Workmentioning
confidence: 99%
“…This organization achieves simultaneous access to the shared cache and eliminated the need for router devices between cores inside the same multi-core cluster. This result was fully presented and explored in the article [3]. An efficient many-core system can be created if an efficient and simple interconnection scheme is provided and that's why the NCSC scheme has been chosen for the MPCAM-based clusters.…”
Section: The Mpcam-based Multi-core Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Content addressable memory (CAM) is a type of AM that accesses memory locations by comparing tags (parts of the content) rather than calculating the address and has certain properties that make it suitable for use as a shared memory [3,6,7]. The use of CAM memory in shared memory for multi-core systems is interesting, as demonstrated by other relevant articles that have recently been published by the authors [8,9].…”
Section: Introductionmentioning
confidence: 99%